2019
DOI: 10.1371/journal.pone.0211230
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes and postoperative pneumonia: An observational, population-based study using the Spanish Hospital Discharge Database, 2001-2015

Abstract: PurposeWe analyzed temporal trends, demographic and clinical characteristics and hospital mortality rates of postoperative pneumonia among type 2 diabetes mellitus (T2DM) patients in Spain from 2001 to 2015. We also compared the incidence, comorbidities and mortality between patients with and without T2DM suffering from postoperative pneumonia. Finally, we analyzed the factors involved in the prediction of in-hospital mortality among patients suffering postoperative pneumonia.MethodsWe used the Spanish Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
2
10
0
1
Order By: Relevance
“…Consistent with previous results, [10][11][12] patients with T2DM were more likely to have postoperative pneumonia after surgery. Unlike previous studies, the incidences of postoperative pneumonia were analyzed in different age groups in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous results, [10][11][12] patients with T2DM were more likely to have postoperative pneumonia after surgery. Unlike previous studies, the incidences of postoperative pneumonia were analyzed in different age groups in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Spanish Hospital Discharge Database shows that T2DM patients had a 21% higher incidence of postoperative pneumonia than nondiabetic patients in 2001-2015. 10 The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database also shows that T2DM was found to be an independent risk factor for postoperative pneumonia in orthopedic surgery. 11,12 Postoperative pneumonia was a major cause of mortality after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous report showed that diabetes mellitus had been linked with an increased risk of infectious disease hospitalization [14]. Former study demonstrated that the incidence of postoperative pneumonia was higher in T2DM patients than in those without this disease [15]. Another study indicated that the long-term mortality in community-acquired pneumonia among patients with undiagnosed diabetes mellitus was higher than patients without diabetes mellitus [16].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have identified numerous patient-related or procedure-related risk factors for POP after femoral neck fracture surgery. In most but not all studies, multiple variables, including older age, male sex, and the presence of several key clinical comorbidities such as chronic obstructive pulmonary disease (COPD), 5 obesity, 7,8 tobacco smoking, 9 prior stroke, 3 impaired preoperative pulmonary function, 10,11 cognitive and functional premorbid status 12 and cardiovascular disease 3 have been identified as risk factors for POP.…”
Section: Introductionmentioning
confidence: 99%